Implementation of Bullying Danger Psychoeducation to Prevent Bullying Behavior among Elementary School Students - Muhammad Kevin Duta Maulana; Ima Fitri Sholichah (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
Bullying behavior remains a serious issue in elementary school settings, particularly in verbal and social forms that negatively affect students’ psychological well-being and the overall school climate. This study aimed to implement and examine the effectiveness of psychoeducation on the dangers of bullying as a preventive intervention among elementary school students. The research employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest format. The participants were sixth-grade students of UPT SD Negeri 26 Gresik who were identified as having tendencies toward bullying behavior. Data were collected through a bullying questionnaire administered before and after the psychoeducational intervention to measure students’ understanding and tendencies related to bullying behavior. Prior to its use, the instrument was tested and confirmed to be valid and reliable for measuring bullying-related constructs. The psychoeducation program was conducted intensively through structured sessions focusing on the definition, forms, psychological impacts, and prevention of bullying. Data analysis using the Wilcoxon Signed Rank Test indicated a significant difference between pretest and posttest results, showing a reduction in bullying tendencies and an increase in students’ awareness and preventive attitudes. These findings demonstrate that psychoeducation on the dangers of bullying is an effective intervention for reducing bullying behavior and fostering prosocial awareness among elementary school students. This study highlights the importance of integrating psychoeducational programs into school-based guidance and counseling services to promote a safe, supportive, and bullying-free school environment.